Characteristics and management of giant cell arteritis in France: a study based on national health insurance claims data. (25th June 2019) - Mahr, Alfred; Belhassen, Manon; Paccalin, Marc; Devauchelle-Pensec, Valérie; Nolin, Maeva; Gandon, Sophie; Idier, Isabelle; Hachulla, Eric
Abstract: Objective: Few data are available on the epidemiology and management of GCA in real life. We aimed to address this situation by using health insurance claims data for France. Methods: This retrospective study used the Echantillon Généraliste de Bénéficiaires (EGB) database, a 1% representative sample of the French national health insurance system. The EGB contains anonymous data on long-term disease status, hospitalizations and reimbursement claims for 752 717 people. Data were collected between 2007 and 2015. The index date was defined as the date of the first occurrence of a GCA code. Demographics, comorbidities, diagnostic tests and therapies were analysed. Annual incidence rates were calculated, and incident and overall GCA cases were studied. Results: We identified 241 patients with GCA. The annual incidence was 7–10/100 000 people ⩾50 years old. Among the 117 patients with incident GCA, 74.4% were females, with mean age 77.6 years and mean follow-up 2.2 years. After the index date, 51.3% underwent temporal artery biopsy and 29.1% high-resolution Doppler ultrasonography. Among the whole cohort, 84.3% used only glucocorticoids. The most-prescribed glucocorticoid-sparing agent was methotrexate (12.0%). Conclusion: The incidence of GCA in France is 7–10/100 000 people ⩾ 50 years old. Adjunct agents, mainly methotrexate, are given to only a few patients. The use of temporal artery biopsy in only half of the patients might reflect a shift toward the use of imaging techniques to diagnose GCA.